In Vitro Evaluation of Phenolics Content, Antioxidant and Antimicrobial Activities of Three Centaurea L. Species from Iran - Roya Karamian*, Rose Eghbalian (Tabriz University of Medical Sciences, 2017)
Background: Members of the genus Centaurea L. (Astraceae) are used in some countries for betterment of various ailments in the popular medicine. The main group of secondary metabolites in plants are phenolic compounds and flavonoids which are the main subset of phenolic compounds, possess a lot of biological properties such as antioxidant activity. The aim of present research is to determine in vitro total phenol and flavonoid contents, antioxidant potency and also antibacterial activity of the methanolic extracts of capitulla and aerial parts of three Centaurea species, namely C. sosnovsky Grossh., C. irritans Wagenitz and C. kandavanesis Wagenitz. In addition, any relationships between the phenolics content and their antioxidant properties were discussed. Methods: To determine total phenol and flavonoid contents of the methanolic extracts, Folin-Ciocalteu and aluminum chloride methods were used, respectively. To evaluate antioxidant activity three different test systems, namely 2, 2-diphenyl-1-picrylhydrazyl free radical scavenging (DPPH), Cu-chelating and ß-carotene/linoleic acid bleaching were used. In addition, disc diffusion method was used to assess antibacterial activity of the extracts against 6 gram positive and negative bacteria. Results: Results indicated that the highest total phenol content (98.91 ± 1.87mg GAE/g of dry extract) represented by the aerial part extract of C. kandavanensis. The highest total flavonoid content (5.382 ± 0.231mg GAE/g of dry extract) and also DPPH radical scavenging activity (IC50; 0.20 ± 2.02 mg/ml) were exhibited by the capitulla extract of C. sosnovsky. However, the aerial part extract of C. irritans had the most potency for β-carotene bleaching (74.74%) among the studied samples. In addition, the extracts had acceptable antibacterial activity against both gram-positive and gram-negative bacteria tested. Conclusion: Overall, high content of phenolic compounds and proper antioxidant activity of the examined Centaurea extracts may suggest them as potent antioxidants for special use in future.